2016
DOI: 10.1038/srep33142
|View full text |Cite
|
Sign up to set email alerts
|

Deep sequencing reveals microbiota dysbiosis of tongue coat in patients with liver carcinoma

Abstract: Liver carcinoma (LC) is a common malignancy worldwide, associated with high morbidity and mortality. Characterizing microbiome profiles of tongue coat may provide useful insights and potential diagnostic marker for LC patients. Herein, we are the first time to investigate tongue coat microbiome of LC patients with cirrhosis based on 16S ribosomal RNA (rRNA) gene sequencing. After strict inclusion and exclusion criteria, 35 early LC patients with cirrhosis and 25 matched healthy subjects were enrolled. Microbio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
105
1
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 96 publications
(108 citation statements)
references
References 42 publications
1
105
1
1
Order By: Relevance
“…It is therefore postulated oral bacterial overgrowth may have a profound effect on intestinal bacterial communities and thus CLD pathogenesis and HCC development. This concept is supported by a recent study that showed a high level of oral microbiota Oribacterium and Fusobacterium in HCC patients [13]. The alteration in gut microbiota composition in HCC is summarized in Table 1.…”
Section: Gut Dysbiosissupporting
confidence: 56%
See 1 more Smart Citation
“…It is therefore postulated oral bacterial overgrowth may have a profound effect on intestinal bacterial communities and thus CLD pathogenesis and HCC development. This concept is supported by a recent study that showed a high level of oral microbiota Oribacterium and Fusobacterium in HCC patients [13]. The alteration in gut microbiota composition in HCC is summarized in Table 1.…”
Section: Gut Dysbiosissupporting
confidence: 56%
“…Microbial gene signatures that relate to energy production, nickel/iron transport, and amino acid transport appear to be altered in HCC patients when compared to healthy controls [13]. Moreover, when compared to cirrhotic patients, fecal samples from HCC patients have shown increased growth of phylum Actinobacteria and 13 genera including Gemmiger and Parabacteroides [14].…”
Section: Gut Dysbiosismentioning
confidence: 98%
“…[43] High-throughput sequencing was performed on an Illumina MiSeq instrument according to the manufacturer's instructions. [43] High-throughput sequencing was performed on an Illumina MiSeq instrument according to the manufacturer's instructions.…”
Section: Methodsmentioning
confidence: 99%
“…forsythia expresses two sialidases, SiaHI and NanH, which are important in bacterial colonization [11]. Oral microbiome composition alters fatty acid metabolism [12] and are not just associated with oral cancer development [13] but also are suspected of promoting esophageal [14,15], pancreatic cancer [16,17], or liver cancer [18]. T. forsythia "contributes to the growth of a partner species, Fusobacterium nucleatum, in co-biofilms" [19].…”
Section: Microbiome (Tab 1)mentioning
confidence: 99%